Analisis Perbandingan Pengaruh Hasil Belajar Informatika Siswa Sebelum Wabah Covid Dengan Setelah Wabah Covid di Jurusan DKV SMK Negeri 10 Medan - Palma Juanta; Nurlaila Rahmadani; Syakirah Ramadhina; Mita Yustika Silitonga; Yohana Simbolon; Iren Jayatry Br Brahmana; Musa Agus Saputra Hutagalung (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
Covid-19 which is endemic in Indonesia has damaged the entire fabric of Indonesian society, one of which is in the field of education. Education in Indonesia has not been able to be carried out normally as usual since mid-March 2020. This research aims to compare student learning outcomes before and after the Covid-19 outbreak in the Visual Communication Design (DKV) Department of SMK Negeri 10 Medan. The type of research that will be used is observational research. with a comparative or longitudinal research design. The population of this study were all students of the DKV Department at SMK Negeri 10 Medan who took Informatics subjects. This research sample was taken using a stratified random sampling method. Researchers used quantitative data analysis techniques. Data analysis shows a significant decline in student informatics learning outcomes after the COVID-19 outbreak compared to before the outbreak. The availability of devices such as computers or tablets and a stable internet connection greatly influences the effectiveness of online learning. Students who receive support and guidance from their families during online learning show better learning outcomes. Interactive teaching methods and the use of various online learning tools can improve student learning outcomes.